Rancang Bangun dan Model Kinetika Pengeringan Jamur Tiram pada Pengering Surya dengan Tiga Kolektor - Simanjuntak, Melvin Emil; Widyawati, Paini Sri (Universitas Nusantara PGRI Kediri, 2023)
Oyster mushroom is a group of food plants that are rich in protein, vitamins and minerals. The weakness of this mushroom is its high moisture content so it rots quickly when stored in fresh conditions. Drying by using solar energy is one of the best options because of its sufficient quantity and low cost. This study proposes a solar dryer with three collectors of 500 mm x 500 mm x 1254 mm each with 4 rack. The drying experimental is using a sample of 1 kg. The best model of drying kinetics is the MMF model with an R value of 0.9950. The moisture extraction rate (MER) was 137 gr/hour under experimental conditions.